Mortality among young nicaraguan immigrants to Costa Rica: an application of geographically weighted statistical regression - Bonilla, Roger E. (2014)
This paper applies a geographically weighted statistical regression (GWR) model to young Nicaraguan immigrant homicides in Costa Rica during the period 1998-2008 and identifies possible covariates. The parameters for the GWR model are:   Yi(g)=β0(g)+β1(g)x1 +β2(g)x2 +...+βk(g)xk +ε,   which may be obtained from the solution of   β(g) = (XT W (g)X)−1 XT W (g)Y.   The GWR model is a more adequate model than the classic models, such as the log-linear Poisson model. In the GWR model, poverty was the most significant variable. The map of the estimators associated with the percentage of poor households suggests that the relationship between poverty and mortality by homicide for young Nicaraguan immigrants is stronger in the Caribbean region and neighboring zones. When the GWR model was run for homicides among young Costa Ricans, this effect was not observed, as it was among Nicaraguan immigrants.